Definition of Terrorism and its impact on Criminal Justice System: A Critical Review - Nazir Wattoo, Khalid (Journal of Public Policy Practitioners, 2022)
Terrorism in Pakistan has various manifestations, which includes sectarian, ethnic, religious, and political hues. The decade of 1990 was marked by sectarian terrorism in Pakistan. The history of previous laws on terrorism showed that the first ever law on terrorism; the Suppression of Terrorist Activities (Special Courts) Act was introduced in 1975, which did not have any definition of the term terrorism, however, it was followed by a few other laws promulgated from time to time, depending on the situations. Nevertheless, Anti-Terrorism Act was promulgated in 1997, in which terrorism was defined as per law, for the very first time in the history of Pakistan. The Act was amended many times to date. There are, however, a few flaws in the definition of terrorism in ATA, 1997; which severely impacted the criminal justice system of Pakistan. Police misuse ATA and registered cases under this law to increase the gravity of this issues, which resulted in the increase of workload on special courts, leading to delays in the dispensation of justice. The prosecution was never independent, as it was envisaged to be. They do not have an active role to play in the cases, while at the time of registration of FIRs, during investigations bringing forth witnesses and forensic evidence before the courts was the prime concern of the prosecutions. There was no regular and effective coordination between all three components of the criminal justice system of Pakistan at the top level. Due to faulty or fake FIRs, due to the absence of witnesses, faulty investigation, and sometimes judicial corruption; the courts dismiss the cases. Thereby, mostly the nominated culprits are released on the orders of the courts. In this scenario, there is a dire need to amend the definition of terrorism in ATA, 1997.